PEMANFAATAN LIMBAH KULIT BAWANG PUTIH (Allium sativum L.) SEBAGAI BAHAN AKTIF PEMBUATAN SABUN CAIR - S, Panji Ratih; R, Sih Wahyu; Fitriyany, Erna; I, Cikra; Calya, Finna; Sari, Septiana (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2023)
Utilization of household waste in Indonesia is still very rarely done, one of which is the use of garlic skin waste. From research by Allemann & Baumann in 2008, garlic skin is rich in antioxidant compounds so it can protect skin cells from free radical damage if used as a skincare product, one of which is liquid bath soap for the body. This research aims to formulate garlic skin extract as liquid soap. The concentration used is 10%. The liquid soap formulation used was 17 g of SLS, 3 g of NaCl, 9 g of Cocamidopropyl Betaine, 9 g of Glycerin, Fragrances, and Dyes to taste. Garlic skin extract liquid soap is evaluated for its physical quality consisting of organoleptic test results in the form of liquid, gum-scented and red-colored, pH test of 8.2, height test and foam stability of 79 mm, moisture content test of 51.12%, specific gravity test of 1.012 g/ml, and irritation test declared non-irritating. The results showed that garlic skin extract liquid soap with a concentration of 10 % had a physical quality that complied with their requirements. This research concludes that garlic skin extracts liquid soap meets the requirements of the physical quality test and safe for the skin because it does not cause irritation to the skin when used.